Analisis Pengaruh Prediksi Kebangkrutan, Leverage, dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern - Mubtadi, Novendi Arkham (JIFA (Journal of Islamic Finance and Accounting), 2020)
This study was conducted to examine whether there is an influence of bankruptcy prediction, leverage, company growth on going concern audit opinion. The study was conducted on non-financial companies covering the agriculture sector, mining sector, basic chemical industry sector, various industrial sector, customer goods sector which was listed on the Indonesia Stock Exchange for the period 2015-2018. This type of research in quantitative. This study with a population of 211 and sample of 35 companies. Data analysis method used in this study is logistic regression analysis using SPSS 24 data analysis tools. Sampling technique using purposive sampling. The result in this study indicate that bankcruptcy prediction effect the going concern audit opinion while the leverage and company growth do not effect the going concern audit opinion. Keywords: Bankcruptcy Prediction, Leverage, Company Growth, Going Concern Audit Opinion